The frontier character in País de Jauja by Edgardo Rivera Martí- nez and Ximena de dos caminos by Laura Riesco - Jurado Urbina, Brayan Jayro Aloysius (2022)
This article proposes a reading of the novels País de Jauja by Edgardo Rivera Martínez and Ximena de dos caminos by Laura Riesco from the notion of frontier character. This is defined as the subject that seeks the integration of the different sociocultural systems represented in the works. In the particular case of both novels, the Andean and the Western will be referred to. To do this, we will rely on Yuri Lotman’s proposal on the semiosphere, which will allow us to recognize the symbolic elements that define both cultures. The recognition of these frontier characters will reveal a marked conflictual tendency that undermines any conciliatory process between the Andean and the Western. From this, we will recognize how both narrative projects are linked in a greater reflection that raises the reformulation of the Andean cultural identity as a result of its interaction with the West.